SINTESIS LAKTOGENIN DARI TETRAHIDROFURAN-3-KARBOKSALDEHIDA DAN 2-ASETIL-γ-BUTIROLAKTON DENGAN KATALIS NATRIUM METOKSIDA - Jeffy Julianus; Laurensius Widi Andhika Putra (Universitas Sanata Dharma, 2013)
Abstract: Acetogenin compound known for its activity as anticancer by inhibited the NADHubiquinone reductase contained in the mitochondria. These compounds with high liphophilicity properties have a weakness in solubility with log P 8.44, so modifications to improve the solubility by maintaining a core group of tetrahydrofuran and γ-lactone as well as shortening the alkyl chain is needed. The modified compounds was lactogenin or 3-(3- (tetrahydrofuran-3-yl) acryloyl) dihydrofuran-2(3H)-one) that have a log P 0.90 and is expected to have a better solubility properties than acetogenin. Lactogenin synthesis was based on cross-aldol condensation reaction by reacting tetrahyrdofuran-3-carbaldehyde and 2-acetyl-γ-butyrolactone using sodium methoxide as catalyst. The synthesized compounds were red solution with specific smell. The TLC result showed the new products at Rf 0.314. The purity test by gas chromatography showed 74.07% purity. The structure elucidation by infrared and mass spectroscopy showed that the synthesized compound was β-hydroxy lactogenin or 3-(3-hydroxy-3-(tetrahydrofuran-3-yl) propanoyl) dihydrofuran-2(3H)-one. Keywords: NADH-ubiquinone oksidoreduktase, lactogenin, cross-aldol condensation reaction, β-hydroxy lactogenin